PENGARUH FAKTOR INTRINSIK DAN EKSTRINSIK TERHADAP MINAT MENGGUNAKAN E-LEARNING - Andini, Aryana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Improving the quality of human resources cannot be separated from one way or another by conducting employee competency training and development. Employee training and development requires analysis so that it is known what factors drive employee interest in learning so that training and development can run effectively and on target. This study aims to determine and analyze the intrinsic and extrinsic factors that affect employee interest in using E Learning, as well as to determine and analyze the effect of self-efficacy so that it strengthens intrinsic and extrinsic factors on employee interest in using E Learning. The research was conducted on employees of PT. Bank Negara Indonesia (Persero) Tbk through a questionnaire made with Googleform and distributed using WhatsApp media randomly to 1,669 employees. The total number of respondents who filled out the questionnaire was 353 employees and tested the hypothesis using the SmartPLS application. The results shown from data processing on SmastPLS are that intrinsic and extrinsic factors have a positive effect on employee learning interest in this case learning by using e-Learning. Employees have great responsibility for their work, desire to achieve achievements and win awards. Employees are also motivated to learn because of the influence of the work environment, peer support, company policies so that they can improve performance and ability to work. The test results on self-efficacy show that employees have the ability to manage time and work so that they can take the time to access e-learning, employees feel confident and confident so that the themes and material presented can be easily understood and applied in daily work.